2008
DOI: 10.1002/adma.200800810
|View full text |Cite
|
Sign up to set email alerts
|

π‐σ‐Phosphonic Acid Organic Monolayer/Sol–Gel Hafnium Oxide Hybrid Dielectrics for Low‐Voltage Organic Transistors

Abstract: Anthryl‐alkyl‐PA (π‐σ‐PA) self‐assembled monolayers (SAMs)/hafnium oxide (HfO2) hybrid dielectrics have been integrated into organic thin film transistors (OTFTs) to achieve operating voltages under −1.5 V. Using π‐σ‐PA SAMs on sol–gel processed HfO2, pentacene‐based OTFTs possess low subthreshold slopes (100 mV dec−1), high on–off current ratios (105–106), and hole mobilities as high as 0.22 cm2 V−1 s−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
146
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 45 publications
3
146
0
Order By: Relevance
“…Some of the SAMs would require relatively long preparation time [12][13][14] and usually the functional head groups of SAMs is dielectric specifi c. It is challenging to develop a universal SAMs suitable for different dielectric insulators. More importantly, the SAM also modifi es the surface energy of the dielectric and affects the crystallinity of the organic semiconductors.…”
mentioning
confidence: 99%
“…Some of the SAMs would require relatively long preparation time [12][13][14] and usually the functional head groups of SAMs is dielectric specifi c. It is challenging to develop a universal SAMs suitable for different dielectric insulators. More importantly, the SAM also modifi es the surface energy of the dielectric and affects the crystallinity of the organic semiconductors.…”
mentioning
confidence: 99%
“…Similar study found poor insulating properties of n-hexylphosphonic acid (C 6 PA) SAM and low transistor field-effect mobility for ndecylphosphonic acid (C 10 PA) SAM [20]. Longer chain C 18 PA and anthryl-alkyl-phosphonic acid SAMs were used to improve the insulating properties of the oxide layers [23,27].…”
Section: -9mentioning
confidence: 88%
“…To date the self-assembled monolayers based on alkyl phosphonic acids [20][21][22][23][24][25][26][27] have been obtained by solution process only. In this paper we present that such monolayers can be prepared by dry method as well.…”
Section: -9mentioning
confidence: 99%
“…Ceramic-based inorganic materials with a high dielectric constant (high-k) can be used as a way to lower the operating voltage of organic TFTs [7][8][9]. However, most high-k materials that are suitable for organic TFTs are processed via deposition techniques and sol-gel methods and require high processing temperatures that are not suitable for plastic substrate application.…”
Section: Introductionmentioning
confidence: 99%